Nanocrystalline silicon thin films by RF plasma enhanced chemical vapour deposition - Han, S.C.; Tong, G.B.; Richard, R.; Meriam Ab, G.S.; Rasat, M.M.; Rahman, S.A. (2006)
A plasma enhanced chemical vapour deposition (PECVD) system was designed and built in-house for the deposition of nanocrystalline silicon thin films. In this work, nanocrystalline slicon thin films were deposited at different rf(radio-frequency) power with the silane to hydrogen partial pressure ratio fixed. X-ray diffraction (XRD) and Raman spectroscopy measurements were done to investigate the structural properties of the films. Optical transmittance measurements were carried out to determine various optical parameters of these films. The rf power showed strong influence on the structural and optical properties of the nanocrystalline silicon films produced.